FORMATION OF MOTIVATIONAL-VALUE COMPONENT OF MATHEMATICAL COMPETENCE OF SECONDARY SCHOOL PUPILS IN THE PROCESS OF TEACHING ALGEBRA - Ганна Гоменюк (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2015)
The problem of formation and development of motivation of secondary school pupils in teaching algebra on the basis of cognitive interest by means of a qualified approach. A task that enrich cognitive interest, revealing the importance of mathematical knowledge in various fields of human activity, containing interesting facts from the history of algebra; disclosed connection of the algebra with other school subjects, revealing innovative ways of substantiation of  theoretical facts.